Reproductive performance of Angus x Hereford and Brahman x Hereford heifers fed to prebeeding target weights - Patterson, D.J.; Corah, L.R.; Simms, D.D.; Brethour, J.R.; Negus, W.R. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Heifer development as effected by nutrition was evaluated in 148 F Angus x Hereford (A x H) and 148 F Brahman x Hereford (B x H) heifers. Heifers within each breed cross were assigned to one of two energy levels and weight groups. Heifers on the low and high energy-level diets were fed to reach 55 or 65%, respectively, of their projected mature body weights by the start of spring breeding. A higher (P<.05) percentage of A x H heifers had reached puberty by the start of spring breeding; however, their average age at puberty was greater (P<.05) than that of B x H heifers. Weight at puberty, for heifers that cycled prior to the start of spring breeding, did not differ between breed groups. Weight of heifers at puberty was greater with the high-energy than with the low-energy diets. Prebreeding body condition scores of heifers on the two energy levels differed (P<.05) more among the A x H females. The A x H heifers had higher (P<.05) fall pregnancy rates than the B x H heifers (89.2 vs 71.9%). Energy level has no significant effect on fall pregnancy rate of A x H heifers, but B x H heifers on the high-energy level had a higher (P<.05) pregnancy rate than those on the low-energy diet.
Keywords: Beef; Reproductive performance; Target weight; Pregnancy rate